Impact of Pulp on the Chemical Profile of Mango Wine - Li, X.; Lim, S.L.; Yu, B.; Curran, P.; Liu, S.-Q. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to assess the effect of mango pulp inclusion (which mimicked the maceration step in grape wine fermentation) on the fermentation dynamics and chemical profile of mango wine, especially the volatiles. The growth of Saccharomyces cerevisiae MERIT.ferm was slower in the mango juice with pulp (uncentrifuged juice), with a corresponding slower reduction in °Brix, relative to the juice without pulp (centrifuged juice). The utilisation of glucose, fructose and sucrose was similar in both uncentrifuged and centrifuged juices, with almost complete consumption. Citric, tartaric, malic, pyruvic and succinic acid were the major organic acids in the wines fermented from both the uncentrifuged and centrifuged juices. Citric acid decreased slightly in the macerated wine. Tartaric and malic acid decreased in both wines. Pyruvic acid increased slightly and succinic acid remained almost constant in both wines. Monoterpenes, as one of the signature aroma compounds in mango juice, decreased dramatically in both wines, but were ten times higher in the macerated wine. Terpenols were at least four times higher in the macerated wine. The macerated wine also produced higher levels of fusel alcohols and acetate esters compared to the nonmacerated wine. On the other hand, the non-macerated wine possessed a higher concentration of mediumchain fatty acids and corresponding ethyl esters. This study indicates that the inclusion of pulp in mango wine fermentation would contribute to the aroma complexity.